Increasing knowledge and attitudes of adolescents related to sexual and reproductive health by using audio-visual media during the covid-19 pandemic - Echi Agnes Claudia; Iis Rahmawati; Dini Kurniawati (Universitas Muhammadiyah Semarang, 2021)
Adolescence is a developmental stage from the transition to adulthood. A cognitive problem that affects adolescence namely the lack of knowledge about reproductive health. The purpose of this study was to explain the effectiveness of health education using audio-visual methods on students' knowledge and attitudes about adolescent reproductive health during the COVID-19 pandemic. This research uses a quasi-experimental design. The results obtained from the 75 respondents who filled out the questionnaire showed that the attitude of the students on the pre-test score was 60,00 and the post-test was 63,45, whereas the students' knowledge on the pre-test score was 15,89 and the post-test is 17,20. From the results of the research carried out with the Wilcoxon test that the Asymp. Sig (2-tailed) is worth 0,0001 where the value is less than <0.005, therefore the hypothesis was accepted. Using audiovisual media is that it will add more real material content and will increase memory retention due to media that is much interesting and easy to remember by the individual, factors that can influence knowledge and attitudes related to reproductive and sexual health in adolescents are knowledge, attitudes and the individual's environment in processing the information obtained. Therefore there is a significant effect of health education with audiovisual methods on increasing the knowledge and attitudes of adolescents related to reproductive and sexual health.